2012
DOI: 10.5897/ijbc10.121
|View full text |Cite
|
Sign up to set email alerts
|

On-farm evaluation of improved Brachiaria grasses in low rainfall and aluminium toxicity prone areas of Rwanda

Abstract: The aim of this study was to determine the production of improved Brachiaria grass in comparison with indigenous Brachiaria under low rainfall and aluminium toxicity areas of Rwanda. Three varieties and five hybrids of Brachiaria grass from CIAT and two local grasses (control) were used for on-farm participatory trials without fertilizer application. Twelve farms were selected in each study area and on each farm ten grasses were established in 2 × 3 m plots. Herbage was harvested six times during the year at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 144 publications
1
20
2
1
Order By: Relevance
“…During participatory research with farmers on sites with low rainfall and acidic soils in 2007, among various Brachiaria commercial cultivars, released hybrids and advanced lines, cv. Mulato-II was preferred because of producing green forage year round without any fertilizer input, high above-ground biomass production, palatability, drought tolerance, quick regrowth, persistence, being a perennial and easy for cut-andcarry (Mutimura and Everson, 2012). Therefore, cv.…”
Section: Rwandamentioning
confidence: 99%
“…During participatory research with farmers on sites with low rainfall and acidic soils in 2007, among various Brachiaria commercial cultivars, released hybrids and advanced lines, cv. Mulato-II was preferred because of producing green forage year round without any fertilizer input, high above-ground biomass production, palatability, drought tolerance, quick regrowth, persistence, being a perennial and easy for cut-andcarry (Mutimura and Everson, 2012). Therefore, cv.…”
Section: Rwandamentioning
confidence: 99%
“…The major limitation of livestock production is the lack of of livestock production is the lack of suitable fodder crops that can produce green forage year round (Mutimura & Everson, 2012). One of the logical approaches to increasing forage production to overcome these problems is pasture improvement by grass and legume mix cropping system (Ajayi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Similar decreases in root growth in response to aluminium were found in Jatropha curcas (Rosado et al, 2012), sorghum (Too et al, 2014), and barley (Tamas et al, 2006) in studies that used a similar methodology (e.g., measuring the root growth in seedlings in paper rolls moistened with aluminium solutions). Studies using hydroponic (Giannakoula et al, 2010;Arroyave et al, 2011Arroyave et al, , 2013Matins et al, 2011;Ramos et al, 2012;Roselló et al, 2015), semi-hydroponic (Colombo et al, 2016), and even growth in soil methods (Mutimura & Everson, 2012) have found similar results, but these methods are expensive and time consuming. Hare and Cress (1997) reported that proline accumulation occurred when wheat was exposed to water deficits, and therefore was a function of osmotic regulation and cellular protection.…”
Section: Discussionmentioning
confidence: 66%
“…Selection has also been done under field conditions (Mutimura & Everson 2012), and using a semi-hydroponic method (Colombo et al, 2016), but these techniques may be expensive, difficult, and time consuming. Other alternatives may include early evaluation using germination tests or early seedling growth under controlled conditions (Custódio et al, 2002;Machado Neto et al, 2004;Custódio et al, 2009;Echer et al, 2010;Rosado et al, 2012), and the evaluation of some effective parameters in the cultivars.…”
Section: Introductionmentioning
confidence: 99%